Study of calcium oxalate stones in adults in Syrian coast - بدا يوسف; محمد كنعان; أيمن حرفوش (Latakia University Journal -Medical Sciences Series, 2024)
Urinary stones are a common disease especially in civil societies. The rate of stone formation during a person life is estimated between 1-15%. Our country is located in the stone belt area, which is a geographical region characterized by high rates of stone formation among its population. It includes: Middle East, North Africa, and South Asia. Calcium oxalate stones are the most common type of stone diagnosed in patients. Aim: Determining the prevalence of calcium oxalate stones in Syrian coast among patients with urinary stones, studying the causes of their occurrence and identifying ways to prevent recurrence. Materials and Methods: A prospective study of urinary stone patients who visited the Department of Urology at Tishreen University Hospital in Lattakia and Al-Basel Hospital in Tartus during 2022 and 2023. A chemical analysis was performed on stones isolated from the patients. The patients with calcium oxalate stones were included in the study which count (574) patients. Results: The study included 574 patients who had stones containing calcium oxalate: 350 male patients and 224 female patients. The most common complaint among patients at diagnosis was flank pain at a rate of 65.6%. urinary tract abnormalities causing stone formation were diagnosed in 7.5% of patients. The most common type of calcium oxalate stones were pure stones at a rate of 41.6%, and the presence of a single or multiple metabolic disorder was recorded in 67.4% of patients. The most common metabolic disorder was hypercalciuria at a rate of 47.1%, followed by hypocitraturia at a rate of 39.4%. No significant association was observed between increased BMI and increased formation of calcium oxalate stones, except for stones mixed with uric acid (P value = 0.04). There is an important relationship between stone recurrence and the presence of important metabolic disorders (hypocitraturia, hyperoxaluria, and decreased urine volume). Conclusions: It is recommended to analyze the components of urinary stones to determine the chemical composition, and apply adequate metabolic study for patients with calcium oxalate stones to determine the cause of stone formation, especially in patients with recurrent stones to prevent recurrence, which reflects a better quality of life for the patient and reduces treatment costs, especially in the stone belt area.